2002
DOI: 10.1097/00006123-200204000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Neuronavigation by Intraoperative Three-dimensional Ultrasound: Initial Experience during Brain Tumor Resection

Abstract: Intraoperative 3-D ultrasound seems to provide a time- and cost-effective way to update high-quality 3-D maps used in neuronavigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
145
0
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 253 publications
(154 citation statements)
references
References 36 publications
0
145
0
9
Order By: Relevance
“…5,15,26) However, these imaging techniques are limited by factors such as manpower, cost, and restricted surgical access. 2,7,24) US scanners have been used for intraoperative imaging for 20 years. However, US has not entered common use due to the limited image quality and user-dependent results.…”
Section: Discussion I Problems Of Conventional Navigation Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,15,26) However, these imaging techniques are limited by factors such as manpower, cost, and restricted surgical access. 2,7,24) US scanners have been used for intraoperative imaging for 20 years. However, US has not entered common use due to the limited image quality and user-dependent results.…”
Section: Discussion I Problems Of Conventional Navigation Systemsmentioning
confidence: 99%
“…Recently, 3D US, which provides improved image quality, has been used in intracranial surgery, 9) and 3D USlinked navigation systems have been developed and applied in intracranial surgery. 9,24) Single rack navigation systems with an integrated US scanner have also been reported, 9,22) although our navigation system used an external US scanner connected to the navigation system.…”
Section: S Ohue Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound has also been found efficient as a 'stand-alone' imaging modality for the guidance of endoscopes (34,35) and the evacuation of haematomas (36). Other research groups have also found ultrasound useful for guidance and resection control, alone or in combination with preoperative images in neuronavigation (37)(38)(39)(40)(41), but few groups have explored the potential of this imaging modality for updating preoperative images, as demonstrated in the present work. The present paper demonstrates algorithms that update preoperative image data for accurate display of this important data in the navigation system throughout surgery, when anatomy shifts and changes.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore during tumour resection, neurovascular structures shiftis occurred. Neuronavigation integrated with micro-doppler supply real time images and resolve the brain shift problem [24]- [27].…”
Section: Discussionmentioning
confidence: 99%